VD_FINDINFO HC / 2009 / 65 vom 19. Dezember 2008 - VD Tribunal cantonal (2008)
VIOL, PARTIE CIVILE, AVOCAT, STAGE | 190 al. 1 CP, 411 let. h CPP, 411 let. i CPP, 411 let. j CPP, 415 CPP, 22 al. 2 LPAv, 23 LPAv